Analysis of the challenges faced by municipalities in implementing municipal property rates Act no 6 of 2004 : the case study: three local municipalities within the Dr Kaunda District Municipality in North West Province, South Africa - Kgoete, Oupa (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPA)--Stellenbosch University, 2022.